Evaluation of molecular characterization and phylogeny for quantification of Acanthamoeba and Naegleria fowleri in various water sources, Turkey - Aykur, Mehmet; Dagci, Hande (PLOS ONE, 2021)
Free-living amoeba (FLA) is widely distributed in the natural environment. Since these amoebae are widely found in various waters, they pose an important public health problem. The aim of this study was to detect the presence of Acanthamoeba, B. mandrillaris, and N. fowleri in various water resources by qPCR in Izmir, Turkey. A total of (n = 27) 18.24% Acanthamoeba and (n = 4) 2.7% N. fowleri positives were detected in six different water sources using qPCR with ITS regions (ITS1) specific primers. The resulting concentrations varied in various water samples for Acanthamoeba in the range of 3.2x105-1.4x102 plasmid copies/l and for N. fowleri in the range of 8x103-11x102 plasmid copies/l. The highest concentration of Acanthamoeba and N. fowleri was found in seawater and damp samples respectively. All 27 Acanthamoeba isolates were identified in genotype level based on the 18S rRNA gene as T4 (51.85%), T5 (22.22%), T2 (14.81%) and T15 (11.11%). The four positive N. fowleri isolate was confirmed by sequencing the ITS1, ITS2 and 5.8S rRNA regions using specific primers. Four N. fowleri isolates were genotyped (three isolate as type 2 and one isolate as type 5) and detected for the first time from water sources in Turkey. Acanthamoeba and N. fowleri genotypes found in many natural environments are straightly related to human populations to have pathogenic potentials that may pose a risk to human health. Public health professionals should raise awareness on this issue, and public awareness education should be provided by the assistance of civil authorities. To the best of our knowledge, this is the first study on the quantitative detection and distribution of Acanthamoeba and N. fowleri genotypes in various water sources in Turkey.